A perspective on carbon footprint of decentralized manufacturing of lithium-ion cells industrialization - Jayadevan, Aswani; Pulluru, Mannav; Duggapogu, Ebenezer; Madukkuri, Satyanarayana; Erabhoina, Harimohan; Mandava, Jagadish (Frontiers in Environmental Science, 2026)
Lithium-ion cells are in high demand worldwide due to the rise in EVs, green energy storage, and consumer electronic devices. Establishing a decentralized manufacturing ecosystem for LIB cells is essential as local public and private firms strive to become major participants in this sector. This research article focuses on the carbon footprint of producing current lithium-ion batteries (LIBs; LFP ̴152 kgCO2eq/kWh, NMC811 ̴ 205 kgCO2eq/kWh and NMC622 ̴202 kgCO2eq/kWh, respectively), discusses on different stage of sustainable manufacturing ecosystem, and investigates the carbon footprint dependency on decentralized manufacturing in any geographic area. As a result of this the overall emissions generated across all production steps of lithium-ion cells may be expected to reduce about 6%–7% by 2030.